Rabies seasonality in bats (Chiroptera, Mammalia) from Northwest of Sao Paulo state, Brazil (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is an important zoonosis which has the bats as one of the main reservoirs of the viral agent. In the XXI century still causes huge financial losses to the livestock industry and public health in Latin America, although it is a disease that has prevention, by preventive vaccination in cattle and human populations in risk areas, and post exposition treatment with serum in human beings. Considering the importance of the disease, the objective of this study was to test statistically the correlation between its occurrence in bats and seasonality (rain precipitation) in the northwest of São Paulo, Brazil. To test this hypothesis we used the records of results diagnostic for samples of bats that were sent for examination to the Rabies Laboratory at UNESP (Araçatuba Campus), by health or agriculture teams services of the municipalities in the northwestern region of São Paulo, Brazil. Some samples came from bats found inside the houses or in the streets by the general population or captured by the staff of the Laboratory of Chiroptera, UNESP (Araçatuba Campus), between the years 1999 and 2010, in the same region. The rainfall data were provided by the station of INMET (Institute of Meteorology) Votuporanga in the same period. For statistical analysis the data were grouped in periods of rain (October-March) and dry (April to September), year to year, and we used the Spearman correlation coefficient to test the correlation between rainfall and the occurrence of rabies in bats. The analysis resulted in a negative and significant correlation using the average rainfall during the dry and rainy seasons and the rabies positivity (p = 0.0185, R = – 0.477, N = 24). Therefore, the positivity of rabies increases during the dry season. The weak but significant negative correlation between rainfall and the occurrence of rabies suggests that this is one of the factors that affect the temporal distribution of this zoonosis in bats in the northwestern region of São Paulo, Brazil. It is argued here, by hypothesis, that during the dry seas on the dislocation of bat populations from their shelters occurs due to the water scarcity and resources, and also due to the formation of new colonies by young bats that leave their original shelters. These displacements lead to dispersion of the virus to new areas, as well as an increase in the intraspecific and interspecific interactions of bat populations, that will compete for spaces in shelters, and consequently resulting an increased occurrence of rabies in different species. In addition to rainfall, other factors and processes probably affect or determine the distribution and occurrence of rabies, including the availability of shelters and resources, and the methods for control of hematophagous species.